Treatment of mandibular symphysis fractures in a pregnant domestic cat - Gustina, Dianita; Adni, Izza Nurul; Iseki, Ernesta Quevara; Muhana, Sulthon Aqil; Baihaqie, Riefky Pradipta; Hiroyuki, Andi (ARSHI Veterinary Letters, 2023)
A pregnant domestic cat was found in an accident and taken to the Cikole Animal Hospital at Bandung. Physical examination showed that the cat’s body temperature was 35.6℃ and bleeding was found in the eyes, nose, and mouth. Palpation of the dexter and sinister mandibular bones showed loose bones, and palpation of the abdomen showed that the fetus was still moving. Radiographic examination of the head showed that in the dorsoventral position, the mandibular bones were visible at the right and left mandibular symphysis separated by a radiolucent border. The cat was diagnosed with fracture of the mandibular bone symphysis. Therapy is performed by orthopedic surgery through the installation of a wire or surgical wire to connect the two dexter and sinister mandibular bones. After surgery, cats are administered antibiotics, anti-inflammatories, and multivitamins, with special consideration for pregnancy conditions. The dexter and sinister mandibular bones were fixed on the 8th day after surgery.